2015
DOI: 10.3945/ajcn.115.115295
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of 25-hydroxyvitamin D status during pregnancy: the importance of vitamin D supplementation

Abstract: There is a moderate tracking of 25(OH)D status through pregnancy; factors such as vitamin D supplementation, weight gain, and physical activity are associated with changes in season-corrected 25(OH)D from early to late gestation. These findings have implications for study designs and analyses and approaches to intervention studies and clinical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 31 publications
6
42
0
Order By: Relevance
“…This model explained about 20% of the variation in season-corrected change in 25(OH)D during pregnancy. Moon et al showed that vitamin D supplementation is related to changes in 25(OH)D between the first and the third trimester, which supports our findings [12]. However, we did not observe the effects of gestational weight gain on 25(OH)D change seen in that study.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This model explained about 20% of the variation in season-corrected change in 25(OH)D during pregnancy. Moon et al showed that vitamin D supplementation is related to changes in 25(OH)D between the first and the third trimester, which supports our findings [12]. However, we did not observe the effects of gestational weight gain on 25(OH)D change seen in that study.…”
Section: Discussionsupporting
confidence: 87%
“…This pattern was also seen for the subgroup born in Africa and Asia. Why season would have greater influence on serum concentrations of 25(OH)D in late pregnancy is uncertain, but a similar pattern was also indicated by Moon et al who performed a similar season-correction of 25(OH)D concentrations [12]. …”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…However, our samples were collected up to a week after birth, and it is possible that 25(OH)D concentration might have decreased slightly during this week after birth as exclusive breastfeeding is a predictor of vitamin D deficiency among infants [41]; and in Denmark, <5% of infants are not being breastfed at the time of hospital discharge [42]. However, the tracking of 25(OH)D during pregnancy was previously shown to be moderate [43] and half-life of 25(OH)D is 2-3 weeks; furthermore, vitamin D supplementation for infants is recommended after age 2 weeks; therefore not affecting neonatal 25(OH)D concentrations [44]. Hence, we can be assured that our measurements are a good indicator of the vitamin D concentration in the last month of pregnancy.…”
Section: Discussionmentioning
confidence: 99%